Nonlinear FEA for ultimate strength behavior of Corrosion damaged RC Beam - Devi, A. Kanchana; Ramanjaneyulu, K. (Journal of Structural Engineering, 2024)
Nonlinear finite element analysis (NFEA) is used effectively by various researchers to model the effects of corrosion on the load carrying capacity of RC members. In this paper, details of review on various modelling aspects of corrosion are presented. Also, nonlinear finite analysis is employed to assess nonlinear behaviour of the reinforced concrete beam with and without corrosion. The effects of corrosion are represented in the finite element model by modifying the mechanical properties of reinforcement steel. Load versus displacement behavior is obtained for the RC beam with and without corrosion. Typical crack patterns obtained from NFEA are also presented.